Medium-term peak shaving operation of cascade hydropower plants considering water delay time. (December 2021) - Liao, Shengli; Liu, Huan; Liu, Zhanwei; Liu, Benxi; Li, Gang; Li, Shushan
Abstract: Extreme weather lasting for 5–15 days not only brings large inflows in the medium-term but also causes sharp fluctuations in the daytime load of the power grid which imposes considerable challenges to the modeling and solving of medium-term power grid scheduling. The complex nonlinear constraints and water delay times of cascade hydropower plants significantly increase the difficulty of finding solutions. Hence, this study first advocates an accurate optimization model for determining the medium-term peak shaving operation of cascade hydropower plants considering the water delay time. The objective is to minimize the variance of the remaining load and maximize energy production that aims to regulate the load fluctuation and enhance hydropower efficiency. Then, to describe the water delay time of cascade hydropower plants, a piecewise delay time method (PDTM) is proposed based on the water balance equation. Finally, cascade comprehensive benefits (CCB) are established to alleviate the deviations from the scheduling plan and actual plan affected by the lag time. The developed model is implemented on the eleven cascade hydropower plants of the Lancang River in China. Simulation results demonstrate that the model is able to provide more realistic and executable generation scheduling while obtaining larger hydropower generation benefits and good peak shaving performance. Highlights: Piecewise delay time method describes medium-term water delay time relationship. Medium-term peak shaving model coupling lag time makes realistic generation plan. Cascade comprehensive benefits reduce scheduling deviation and promote generation. Multiobjective model has good peak shaving performance and enhances generation.